2011
DOI: 10.1128/jb.00041-11
|View full text |Cite
|
Sign up to set email alerts
|

Natural Transformation of Myxococcus xanthus

Abstract: Myxococcus xanthus belongs to the delta class of the proteobacteria and is notable for its complex life-style with social behaviors and relatively large genome. Although previous observations have suggested the existence of horizontal gene transfer in M. xanthus, its ability to take up exogenous DNA via natural transformation has not been experimentally demonstrated. In this study, we achieved natural transformation in M. xanthus using the autonomously replicating myxobacterial plasmid pZJY41 as donor DNA. M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…A further transformation performance of p15A-Tp-CF in M. xanthus DK1622 strain yielded 30 correct transformants from 59 antibiotics-resistant colonies. We also performed transformations in SW504, a difA mutant of M. xanthus DK1622 [ 22 , 23 ], from which 4 correct transformants were obtained. Figure 2 c demonstrates some PCR amplification results.…”
Section: Resultsmentioning
confidence: 99%
“…A further transformation performance of p15A-Tp-CF in M. xanthus DK1622 strain yielded 30 correct transformants from 59 antibiotics-resistant colonies. We also performed transformations in SW504, a difA mutant of M. xanthus DK1622 [ 22 , 23 ], from which 4 correct transformants were obtained. Figure 2 c demonstrates some PCR amplification results.…”
Section: Resultsmentioning
confidence: 99%
“…Our population-genomic approach did not allow us to distinguish between the latter two hypotheses, especially as the mechanisms by which recombination in M. xanthus occurs are largely unknown. Natural transformation has been achieved under artificial conditions ( Wang et al , 2011 ) and M. xanthus- specific transducing phages have been isolated ( Martin et al , 1978 ) but no conjugation-mediated recombination has been found. However, it is unclear what mechanisms primarily drive recombination in nature.…”
Section: Discussionmentioning
confidence: 99%
“…6A), suggesting that the presence of eDNA and its interaction with EPS is highly relevant to strength of biofilm ECM and survival under adverse environments. In addition, EPS has been shown to be an extracellular barrier and able to block the plasmid transformation in M. xanthus [50]. This may occur through the EPS interaction with eDNA which would lower DNA local effective concentration, thus allowing only cells deficient in EPS production to be naturally transformable.…”
Section: Discussionmentioning
confidence: 99%